Mental Health and Coping Among Bangladeshi Field Journalists: A Mixed-Methods Study of Trauma and Resilience - Islam, Md Raisul; Anwarus Salam, Muhammad (Universitas Negeri Yogyakarta, 2025)
The research offers insight into news outlets to explain how traumatic incidents are presented in Bangladeshi field journalism, and it, therefore, fills a significant gap in the media studies of Global South. It is one of the earliest attempts of its sort to embrace a mixed-methods approach to such a study. In a bid to expose themselves to psychological harm, journalists usually play first responder during situations involving pandemics, protests, and disasters. Even though there has been a report of high prevalence of PTSD, depression and burnout internationally, there has been sparse systematic data on the same in South Asia. It is a mixed-methods study that will investigate findings on how reporting of traumatic events, such as the COVID-19 epidemic, political instability, and industrial accidents, affected the Bangladeshi field journalists in their mental health in the period 2020-2025. Consecutive survey of 100 reporters and 15 interview qualitative interviews showed that 10% respondents fit the PTSD aspects (PCL-5 ≥33) to 15% moderate to severe depression (PHQ-9 ≥10), 20% with anxiety disorder (GAD-7 ≥10) and 30% with burnouts (MBI≥27). It was also discovered that two-thirds of journalists were accompanied by symptoms of great depressive level, and a significant percentage of journalists took maladaptive coping measures such as using substances (30%), and avoidance (55%). The institutional help, nonetheless, is little, indicating the dire necessity of introducing trauma-aware mental health services to the media sector. It did not have any institutional backing up till 2025 when programs such as Khola Janala counseling and gender-based para-counselor were established but still very few. The evidence suggests that Bangladeshi journalists are at risk with mental health equivalent to war correspondents, but with no systemic coverage and PRISM has not been established, counseling services, trauma-related newsroom changes, and stigma reduction initiatives are urgently needed to maintain the freedom of the press.